2021
DOI: 10.1049/mna2.12066
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic synthesis of copper oxide nanoparticles using leaf extracts of Cissus quadrangularis and Piper betle and its antibacterial effects

Abstract: Owing to its environment-friendly, biocompatible, non-toxic nature of nanoparticles attained from green plant extract, it has remarkable significance in the field of nanotechnology towards effective biomedical application. This work reports the synthesis of copper oxide nanoparticles by means of Cissus quadrangularis and Piper betle via greensynthesis route. The medicinal leaf extracts possessing phytochemicals such as alkaloids and polyphenols act as a reducing agent in the current synthesis. The characteriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…2023, 14, x FOR PEER REVIEW 9 of 17 findings indicated the existence of phytochemicals such as alkaloids, tannins, carboxylic acids, flavonoids, and proteins within the whole-cell leaf extract of CQ. These results were also consistent with the major peaks involved in the original leaf exacts of CQ, as previously reported [39].…”
Section: Isolation Of Exosomessupporting
confidence: 92%
“…2023, 14, x FOR PEER REVIEW 9 of 17 findings indicated the existence of phytochemicals such as alkaloids, tannins, carboxylic acids, flavonoids, and proteins within the whole-cell leaf extract of CQ. These results were also consistent with the major peaks involved in the original leaf exacts of CQ, as previously reported [39].…”
Section: Isolation Of Exosomessupporting
confidence: 92%
“…These findings reveal the existence of phytochemicals such as alkaloids, tannins, carboxylic acids, flavonoids, and, proteins within the whole-cell leaf extract of CQ. These results were also comparable to the major peaks involved in the original leaf exacts of CQ as indicated before [36].…”
Section: Fourier Transform Infrared Spectroscopysupporting
confidence: 86%
“…Similarly, Rautela et al [69] also reported that the AgNPs synthesized from Tectona grandis seeds extract have a mean particle size of 20 nm. A study conducted by Kasi et al reported the results obtained by TEM analysis for the particle size of CuONPs synthesized using leaf extract of Piper betle were in the range of 20-40 nm [70].…”
Section: Discussionmentioning
confidence: 99%